As mídias e os modos de ser criança e se relacionar com a infância na contemporaneidade - Toia, Patrícia Vieira de Souza (2013)
This dissertation addresses the media discourses on the several ways of being a child and relating with one's childhood. An analysis of these modes of existence is carried out from the discourses conveyed in different media vehicles: in print magazines such as "Crescer", "Pais & Filhos" and "Veja", and TV broadcasting programmes on open channels such as "Globo" and "Record". Based on the theoretical and methodological work of Foucault, this study discusses and utilizes the notions of modes of subjectivation and "governmentality", aiming to analyze the strategies at work in media that allow the creation of hegemonic ways of being and relating to one's childhood through statements of consumption and knowledge; it also identifies what is constituted as an object of consumption and knowledge for children, and discusses the nature of these normalizing practices by analyzing the "models" of childhood and children produced by them. Therefore, a study was conducted regarding the historical construction of the different notions of being a child and the different ways of relating to one's childhood. Then, an analysis of the ongoing media strategies in the materials was carried out, revealing the way through with such models are built from a set of standards and practices entangled in strength games of power and knowledge. Finally, we question – from a genealogical study – the practices of knowledge-power-subjectivation in media materials, aiming to give visibility to the discontinuities of these modes of existence in the contemporary world through the vectors of consumption and knowledge. With that, the dispositif of media was considered as one of the agents that combine discourse modelers from a system of rules, which tell us about a notion of childhood as a phase transition into the adult's world, as incompleteness, however, at the same time, they present children as competent, autonomous and able, projecting on them skills that characterize what is traditionally defined as the adult world, particularly in relation to technology and consumption practices.